On the laplace transforms of the first hitting times for drawdowns and drawups of diffusion-type processes - Pavel V. Gapeev; Neofytos Rodosthenous; V. L. Raju Chinthalapati (Risks, 2019)
We obtain closed-form expressions for the value of the joint Laplace transform of the running maximum and minimum of a diffusion-type process stopped at the first time at which the associated drawdown or drawup process hits a constant level before an independent exponential random time. It is assumed that the coefficients of the diffusion-type process are regular functions of the current values of its running maximum and minimum. The proof is based on the solution to the equivalent inhomogeneous ordinary differential boundary-value problem and the application of the normal-reflection conditions for the value function at the edges of the state space of the resulting three-dimensional Markov process. The result is related to the computation of probability characteristics of the take-profit and stop-loss values of a market trader during a given time period.
Keywords: 330; boundary-value problem; diffusion-type process; first hitting time; Laplace transform; normal reflection; running maximum and minimum processes